Factors Affecting Students' Desire to Save in The Bank (Observation on Senior High School Yadika 11, Bekasi) - Sari, Rachi Titi Ramadhani; Puspitarini, Sari (Universitas Mercu Buana, 2021)
Abstract. The purpose of this research was cultivate of student interest on saving in SMA Yadika 11 Bekasi, approaching from financial literacy and financial inclusion variables. The population used in this research is the students of SMA Yadika 11 Bekasi. Sampling in this research was determined through a questionnaire using the probability sampling method. Sample for this research obtained 120 respondents. Analized data method used is SEM (Structural Equation Model) from SPSS 23. Result from this research is financial literacy had a significant positive effect on students' interest in saving at SMA YADIKA 11 Bekasi, so do financial inclusion had a significant positive effect on students' saving interest in YADIKA 11 SMA Bekasi.